Effectiveness of Instructional Program for Nurses’ Knowledge regarding Oxygen Administration Methods at Pediatric Teaching Hospitals in Mosul City (Medico Legal Update, 2020)
The Objective: To evaluate the effectiveness of instructional program for nurses’ knowledge regardingoxygen administration methods at pediatric teaching hospitals in Mosul City.The Methodology: A quasi-experimental study was applied at pediatric teaching hospitals in Mosul Cityfrom 21 of October/ 2018 till 17 of July / 2019. The selection of the sample was using the non- probability(Purposive) sample that chosen for the current study. The total study sample consisted of (52) nurses,(26) nurses working in the Al-Kansaa Teaching Hospital and (26) nurses working Ibn Al-Atheer TeachingHospital from Mosul City. The program lectures and questionnaire were constructed and provided fornurses to evaluate the effect of the instructional program on nurse’s knowledge. The Pearson’s coefficientof correlation result are (r= 0.756) and are significant at p ? 0.05 level was used to estimate the scale (test –retest) by using SPSS version 25.Results shows that statistical differences (paired samples t-test) of the knowledge for the study and controlgroup concerning the oxygen administration methods for pediatric. There are high significant relationshipsbetween pre-test and post-test result for study group. But are not significant relationships between pre-testand post-test result for control group at P.value ? 0.05 levels.